2001
DOI: 10.1016/s0008-6363(01)00220-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of transcription factor NF-κB reduces matrix metalloproteinase-1, -3 and -9 production by vascular smooth muscle cells

Abstract: NF-kappaB is required for cytokine upregulation of MMP-1, -3 and -9 in VSMCs, which suggests that NF-kappaB inhibition may promote plaque stabilisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
217
1
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(237 citation statements)
references
References 47 publications
16
217
1
3
Order By: Relevance
“…This phenomenon is closely similar to that observed in COPD patients and in mice with emphysema induced by cigarette smoke or gene knockout (23,(47)(48)(49)(50). Taking account of the fact that the promoter regions of the MMP2 and MMP9 genes contain binding sites for NF-B for their transcriptional regulation (8,9), the increased expression of MMP-2 and MMP-9 in Ig-Hepta Ϫ/Ϫ mice is likely to be mediated through ROS-dependent NF-B activation. Because MMP-12 expression is also regulated by ROS and NF-B (51, 52), the up-regulation of MMP-12 observed in Ig-Hepta Ϫ/Ϫ mice may be mediated via a similar mechanism.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This phenomenon is closely similar to that observed in COPD patients and in mice with emphysema induced by cigarette smoke or gene knockout (23,(47)(48)(49)(50). Taking account of the fact that the promoter regions of the MMP2 and MMP9 genes contain binding sites for NF-B for their transcriptional regulation (8,9), the increased expression of MMP-2 and MMP-9 in Ig-Hepta Ϫ/Ϫ mice is likely to be mediated through ROS-dependent NF-B activation. Because MMP-12 expression is also regulated by ROS and NF-B (51, 52), the up-regulation of MMP-12 observed in Ig-Hepta Ϫ/Ϫ mice may be mediated via a similar mechanism.…”
Section: Discussionsupporting
confidence: 81%
“…They release various inflammatory mediators, including tumor necrosis factor (TNF)-␣, monocyte chemotactic protein (MCP)-1, and reactive oxygen species (ROS), which promote pulmonary inflammation (4 -6). It has been shown that ROS induce expression of macrophage matrix metalloproteinases (MMPs), including MMP-2, MMP-9, and MMP-12, through activation of the transcription factor nuclear factor-kappa B (NF-B) (7)(8)(9)(10)(11). MMPs are a family of Ca 2ϩ -activated Zn 2ϩ -dependent proteases that degrade the extracellular matrix, such as collagens, elastins, and gelatin (12).…”
mentioning
confidence: 99%
“…For instance, it has been reported that EGCG inhibits the chymotrypsin-like activity of the proteasome, with IC 50 values in the range 86-194 nM, and subsequent accumulation of IjB-a [55]. This would result in inhibition of NF-jB activation and in downstream inhibition of NF-jB-regulated genes such as the matrixins [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…α-Lipoic acid (ALA, 1,2-dithiolane-3-pentanoic acid) is a naturally occurring antioxidant which inhibits TNF--induced NF-B activation and acts as a direct free-radical scavenger (Packer et al, 1995;Zhang and Frei, 2001). The promoter region of MMP-9 contains binding sites for NF-B (Sato and Seiki, 1993) and MMP-9 expression has been shown to be regulated by NF-B (Rajagopalan et al, 1996;Bond et al, 2001). Thus, we hypothesized that ALA α-Lipoic acid inhibits matrix metalloproteinase-9 expression by inhibiting NF-κB transcriptional activity may inhibit MMP-9 expression by inhibiting NF-B activation.…”
Section: Introductionmentioning
confidence: 99%